Substance P-loaded electrospun small intestinal submucosa/poly(ϵ-caprolactone)-: ran -poly(l-lactide) sheet to facilitate wound healing through MSC recruitment - Kim, Min Ju; Ji, Yun Bae; Seo, Ji Young; Park, Seung Hun; Kim, Jae Ho; Min, Byoung Hyun; Kim, Moon Suk (Journal of Materials Chemistry B, 2019)
In this work, we prepared an electrospun small intestinal submucosa/poly(ϵ-caprolactone)-ran-poly(l-lactide) (SIS/PCLA) sheet onto which substance P (SP) was loaded, and this was employed as a cell-free scaffold for wound healing through the mobilization of human mesenchymal stem cells (hMSCs). SP release from the SP-loaded scaffold was 42% at 12 h and 51% at 24 h due to an initial burst of SP, but after 1 day, it exhibited a linear release profile and was released at a sustained rate for 21 days. The SP-loaded SIS/PCLA sheet exhibited higher in vitro and in vivo hMSC migration than did the PCLA and SIS/PCLA sheets. Large hMSCs injected into the tail vein of mice models migrated towards the wound to a greater extent in the presence of the SP-loaded SIS/PCLA sheet than with the PCLA and SIS/PCLA sheets, as confirmed by the CD44 and CD29 markers of recruited hMSCs. In animal wound models, significantly higher wound contraction (∼97%) in the group treated with the SP-loaded SIS/PCLA sheet was observed compared with the PCLA (∼74%) and SIS/PCLA (∼84%) groups at 3 weeks. In addition, SP-loaded SIS/PCLA-treated animals showed significant epidermal regeneration and collagen density (56%) in the mature granulation tissue at 3 weeks compared to the PCLA and SIS/PCLA groups. The wound area after SP-loaded SIS/PCLA sheet treatment also showed high blood vessel formation at the early stage, resulting in enhanced wound healing. Furthermore, the SP-loaded SIS/PCLA group exhibited a lower macrophage count (2.9%) than did the PCLA (7.7%) and SIS/PCLA (3.4%) groups. It was thus confirmed that the use of SP-loaded SIS/PCLA sheet as a cell-free scaffold could effectively enhance wound healing through MSC recruitment.
Keywords: Electrospuns; Human mesenchymal stem cells (hMSCs); Poly (l-lactide); Release profiles; Small intestinal submucosa; Vessel formation; Wound contraction; Wound healing; Animals; Cell Movement; Female; Hyaluronan Receptors; Intestinal Mucosa; Mesenchymal Stem Cells; Mice; Mice, Nude; Polyesters; Skin; Spectroscopy, Near-Infrared; Substance P; Wound Healing